Identifying the Differences in Symmetry of the Anthropometric Parameters of the Upper Limbs in Relation to Manual Laterality between Athletes Who Practice Sports with and without a Ball - Badau Adela; Badau Dana (Symmetry, 2024)
The purpose of this study was to identify the asymmetries between the dimensions of the upper limbs, in relation to manual laterality, of the athletes who practice team sports with a ball and those who practice other sports without a ball. We consider the fact that ball handling influences the development of anthropometric parameters at the level of the upper limbs and especially at the level of the hand in correlation with the execution technique and with the characteristics of the practiced sport. This study included 161 student-athletes, who were male and right-handed, divided into two groups: the group of athletes practicing ball sports (G_BS) with 79 (49%) subjects and the group of athletes practicing non-ball sports (G_NBS) with 82 (51%) subjects. The anthropometric measurements of the upper limbs were performed on both sides (right and left): upper limb length, hand length, palm length, hand breadth, hand span, pinky finger, ring finger, middle finger, index finger and thumb. The most relevant symmetries, between the two groups, were recorded in the following anthropometric parameters on the right side (recording the smallest average differences): ring finger 0.412 cm and thumb 0.526 cm; for the left side, they were the ring finger 0.379 cm and thumb 0.518 cm. The biggest asymmetries between the two groups were recorded, for both the right and left sides, for the following parameters: upper limb length > 6 cm; hand span > 2 cm; and hand length > 1 cm. For all the anthropometric parameters analyzed, the athletes from the ball sports group (G_BS) recorded higher average values than those from the other group (G_NBS) for both upper limbs. The results of this study reflect the fact that handling the ball over a long period of time, starting from the beginning of practicing the sport until the age of seniority, causes changes in the anthropometric dimensions of the upper segments, causing asymmetries between the dominant (right) and the non-dominant (left) side.
Keywords: anthropometric asymmetries; sports with ball; sports without ball; right and left upper limbs; longitudinal and transversal dimensions; human body symmetry